A guide to problem solving [for] Mathematics for elementary teachers : a contemporary approach - Miller, Don. (John Wiley and Sons, 2000)
Guess and test. Use a variable. Draw a picture. Look for a pattern. Make a list. Solve a simpler problem. Draw a diagram. Use direct reasoning...